Nitidine chloride, a benzophenanthridine alkaloid from Zanthoxylum nitidum (Roxb.) DC., exerts multiple beneficial properties, especially in tumors and inflammation-related diseases - Lu, Qiang; Luo, Shuang; Shi, Zhongfeng; Yu, Mingzhen; Guo, Weifeng; Li, Cailan (Frontiers in Pharmacology, 2022)
Plant-derived alkaloids are a kind of very important natural organic compounds. Nitidine chloride is one of the main active ingredients in Zanthoxylum nitidum (Roxb.) DC. which is a frequently-used Chinese herbal medicine for the treatment of gastrointestinal diseases and traumatic injury. At present, there are numerous studies of nitidine chloride with regard to its pharmacology, pharmacokinetics, toxicology, etc. However, a systematic, cutting-edge review of nitidine-related studies is extremely lacking. The present paper aimed at comprehensively summarizing the information on the extraction, separation and purification, pharmacology, pharmacokinetics, toxicology and formulation of nitidine chloride. The knowledge included in the present study were searched from the following academic databases involving Web of Science, PubMed, Google scholar, Elsevier, CNKI and Wanfang Data, till July 2022. In terms of nitidine chloride extraction, enzymic method and ultrasonic method are recommended. Resin adsorption and chromatography was usually used for the separation and purification of nitidine chloride. Nitidine chloride possesses diversified therapeutical effects, such as anti-tumor, anti-inflammation, anti-colitis, anti-malaria, anti-osteoporosis, anti-rheumatoid and so on. According to pharmacokinetics, the intestinal absorption of nitidine chloride is passive diffusion, and it is rarely excreted with urine and feces in the form of prototype drug. Nitidine chloride has a moderate binding rate of plasma protein, which is independent of the drug concentration. As to toxicology, nitidine chloride showed certain toxicity on liver, kidney and heart. Certain new formulations, such as nanoparticle, microsphere and nano-micelle, could increase the therapeutic effect and decrease the toxicity of nitidine chloride. Despite limitations such as poor solubility, low bioavailability and certain toxicity, nitidine chloride is still a promising natural alkaloid for drug candidates. Extensive and intensive exploration on nitidine chloride is essential to promote the usage of nitidine-based drugs in the clinic practice.